Biosorption of Ni (II) from aqueous solution using Acer saccharum leaves (ASL) as a potential sorbent - Ravuri, DR.Hemakrishna; Gilbert, W.B. (International Journal of Advanced Chemistry, 2013)
In this research work Powder of Acer Saccharum Leaves (PASL) were used as a non-conventional, cost-effective sorbent for removal of Ni (II) from aqueous solutions in batch systems. The sorbent was characterised with respect to surface area, pore volume, etc. It was found that PASL has high specific surface area (11.99 m2/g) and contains Ni (II) binding functional groups (e.g. Hydroxyl and Carboxyl).The biosorbent was characterized by FTIR, SEM and X-ray mapping, and the powder surface area was determined by BET. The optimum biosorption conditions were determined as a function of pH, biomass dosage, contact time, and initial metal ion concentration. The maximum Ni (II) biosorption was obtained at pH 4.0. The equilibrium data were better fit by the Langmuir isotherm and Freundlich isotherm models. The kinetic studies indicate that the biosorption process of the metal ion Ni (II) has followed well the pseudo-second order, avrami and intraparticle diffusion models. Keywords: Acer Saccharum Leaves (ASL); Adsorption; Adsorption kinetics; adsorption isotherms; Ni (II) ions.